Arab Canadians NC05 (eHRAF World Cultures, 1999)
Arab Canadians are first-generation Christian or Muslim Arabic-speaking immigrants and their descendants who originally came from the Arab world and have roots in Arabic culture. Arab Canadians can be found throughout Canada, although the largest communities are found in major cities, such as Montreal and Toronto. There are five documents in the Arab Canadians file. The two major works cover the immigrant history, assimilation, and acculturation of Arab Canadians in Canada and Lebanese and Syrian Canadians in Nova Scotia. Three shorter articles examine the changes in Lebanese-Canadian households and families, the persistence of traditional customs in an Edmonton, Alberta Druse community, and a Lebanese community in Lac La Biche, Alberta